Canada : Selected Issues. (IMF Staff Country Reports; Country Report, 2009)
This Selected Issues paper on Canada examines economic development and policies. Capital ratios before the crisis have been a key determinant of bank performance during the turmoil; and Canadian banks had ample capital. Specifically, most banks with critically low capital at end-2006 later experienced dramatic equity value declines, and many had to be rescued. Regulatory and structural factors contributed to the resilience of Canadian banks by reducing their incentives to take risks.